CACAT YURIDIS PUTUSAN HAKIM BERSIFAT NON EXECUTORIAL DALAM PERKARA KORUPSI - Sidik Sunaryo (Komisi Yudisial RI, 2010)
ABSTRACTThe judge verdicts has an opportunity to participate actively in improving the judicial system and image. Therefore, the judge shall consider the juridical, sociological, and psychological aspects in every decision, while still relying on the formal legal provisions and moral, culture, modesty, and religious values in the society. This decision will thus be executorial and legitimate. Instead, the decision that fails to accommodate these things would be viewed as a decision that does not reflect the sense of justice, especially in cases of corruption which have caused financial losses to the economy of the country. Plus, if the judges tend not to maintain their independence, due for example, the strong external pressure, then through a comprehensive review of this decision, the author identifies a number of weaknesses that deserve to be observed. Keywords: corruption, judicial power independence, proof theory, justice. ABSTRAKPutusan hakim memiliki kesempatan untuk berpartisipasi secara aktif dalam meningkatkan sistem dan kesan terhadap peradilan. Agar putusan dapat dilaksanakan dan mendapatkan legitmasi, hakim mempertimbangkan aspek hukum, sosial, dan psikologis di samping aturan hukum, nilai moral, budaya dan keagamaan dalam masyarakat. Sebaliknya, putusan tersebut gagal apabila tidak merefleksikan keadilan khususnya dalam kasus-kasus korupsi yang menyebabkan kerugian keuangan dan ekonomi negara. Selain itu, apabila hakim tidak mampu mempertahankan independendensinya maka akan mendorong munculnya tekanan eksternal dimana sepanjang kajian terhadap putusan ini, penulis mengindentifikasikan kelemahan-kelemahan pantas amati lebih lanjut. Kata kunci: korupsi, independensi kekuasaan kehakiman, teori pembuktian, keadilan.